Analytical study of the sectional behavior and the effective width of T-shaped reinforced concrete walls. (15th June 2021) - Rojas, F.; Massone, L.M.; Hernandez, A.
Highlights: The sectional behavior (strain and stress) in T-shaped reinforced concrete wall is analytically studied. The effective width in T-shaped reinforced concrete wall is analytically studied. An analytic model of the strain profile of the tension flange of T-shaped walls is presented. After initiation of yielding in the flange, the effective width of the flange in tension  grows quickly, concluding that independent of the geometry and the slenderness, this covers the entire section if yielding is expected. Abstract: In this article, the sectional behavior (strain and stress) and the effective width in T-shaped reinforced concrete wall are analytically studied. For the parametric study, a nonlinear quadrilateral thin flat layered shell element with 6 degrees of freedom (DOF) per node for the modeling of reinforced concrete wall structures developed by Rojas et al. (2019) is used, varying the axial load (AL), longitudinal steel ratio of the web (LSRW) and flange (LSRF) boundary, aspect ratio (AR) relative to the length of the web of the wall (lw ) and height of the wall (hw ), and length of the flange (Lf ). The parametric study is used to compare the element response that couple the axial, flexion and shear behavior, with a model that only incorporates the coupling of flexion and axial, maintaining plane sections (flexural model). Based on the parametric study, it is calibrated an analytic model of the strain profile of the tension flange of T-shaped walls. Additionally, by including the effect of shear in the model, amplification of the maximum compression strain and a reduction of the maximum tensile strain in the web is observed, mainly in squat walls. Besides, the parametric study is also used to calculate the effective width of T-shaped walls with the flange in tension, finding that it depends mainly on the length of the flange and the roof drift. After initiation of yielding in the flange, the effective width grows quickly, concluding that independent of the geometry and the slenderness, the effective width of the flange in tension covers the entire section if yielding is expected.